Effect of Copper-Containing Stainless Steel on Apoptosis of Cor-onary Artery Smooth Muscle Cells - Hui Li; Xiaolan Li; Tingjia Cao; Qiang Zhu; Fuyuan Liu; Heng Zhou (Iranian Journal of Public Health, 2021)
Background: We aimed to investigate the effect of copper stainless steel on apoptosis of vascular smooth muscle cells in coronary artery.